EXPRESSING CONTROVERSIAL MEMES IN FIFA WORLD CUP QATAR 2022 EVENT: A CRITICAL MULTIMODALITY DISCOURSE ANALYSIS - Hafif Hafif Priambodo; Khristianto (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study discusses the representation of controversial issues in memes that appeared during the FIFA World Cup 2022 in Qatar, especially those related to human rights violations and the rejection of the LGBTQ community. The research uses a Critical Multimodal Discourse Analysis (CMDA) approach by combining the theory of representational meaning from Kress and van Leeuwen (2006) for the visual aspect and the theory of transitivity from Halliday (2014) within the framework of Systemic Functional Linguistics (SFL) for the verbal aspect. Five memes were purposively selected from various social media platforms, (langsung saja ke sumber data) and analyzed using a descriptive qualitative method. The visual analysis shows the use of various types of representational processes, such as symbolic attributive, symbolic suggestive, transactional narrative, and non-transactional narrative, which express social criticism through symbols, gestures, and spatial arrangements. Meanwhile, the verbal analysis reveals that material, relational, and verbal processes are frequently used to construct meaning and deliver criticism explicitly. This study concludes that memes are not only a form of entertainment but also an effective communication tool to express social and political criticism in a creative and accessible way for global audiences.